Gel electrophoresis of DNA partially denatured at the ends: What are the dominant conformations?. Issue 5 (8th February 2013) - Sean, David; Slater, Gary W.; Gaš, Bohuslav
<x xml:space="preserve">Abstract</x> Gel electrophoresis of a partially denatured dsDNA fragment is studied using Langevin Dynamics computer simulations. For simplicity, the denatured ssDNA sections are placed at the ends of the fragment in a symmetrical fashion. A squid‐like conformation is found to sometimes cause the fragment to completely block in the gel. In fact, this conformation is the principal cause of the steep reduction in mobility observed in the simulations. As the field is increased, it is found that the occurrence of this conformation dominates the migration dynamics. Although the squid conformation seems to be more stable at high fields, the field can eventually force the fragments to thread through the gel pores regardless. We qualitatively explore the behavior of this squid‐like conformation across a range of fields and degrees of denaturation, and we discuss the relevance of our findings for TGGE.